# What is 91 divided by 13 with remainder?

What is 91 divided by 13 with remainder?

7

## Related questions

Description : What is 91 divided by 13 with remainder?

Description : What is 17496 divided by 91 with a remainder?

Description : A sample of natural gas containing 80% methane (CH4 ) and rest nitrogen (N2 ) is burnt with 20% excess air. With 80% of the combustibles producing CO2 and the remainder going to CO, the Orsat analysis in volume percent is (A) CO2 : 6 ... 96, N2 :72.06 (D) CO2 : 7.60, CO : 1.90, O2 : 4.75, N2 : 85.74

Last Answer : (B) CO2 : 7.42, CO : 1.86, O2 : 4.64, N2 :86.02

Description : When x^13 + 1 is divided by x –1, the remainder is : -Maths 9th

Description : If the polynomial x^19 + x^17 + x^13 + x^11 + x^7 + x^5 + x^3 is divided by (x^2 + 1), then the remainder is : -Maths 9th

Description : A box contains 4 green, 5 red and 6 white balls. Three balls are drawn randomly. What is the probability that the balls drawn are of different colours? a) 24/91 b) 67/91 c) 21/91 d) 70/91 e) 3/13

Description : When a number "n" is divided by 5, the remainder is 0 and when three times a number "n" is divided by 5 the remainder is what?

Description : Find the remainder when y3 + y2 - 2y + 5 is divided by y - 5. -Maths 9th

Last Answer : Remainder = 145 Again, we should evaluate p(5) Let p(y) = y3 + y2 - 2y + 5 ∴ p(5) = 53 + 52 - 2 x 5 + 5 = 125 + 25 - 10 + 5 = 145 Thus , we find that p(5) is the remainder when p(y) is divided by y - 5 .

Description : Determine the remainder when polynomial p(x) is divided by x - 2 . -Maths 9th

Last Answer : p(x) = x4 - 3x2 + 2x - 5 According to remainder theorem, the required remainder will be = p(2) p(x) = x4 - 3x2 + 2x - 5 ∴ p(2) = 24 - 3(2)2 + 2(2) - 5 =16 - 12 + 4 - 5 = 3

Description : If x51 + 51 is divided by x + 1, then the remainder is -Maths 9th

Last Answer : (d) Let p(x) = x51 + 51 . …(i) When we divide p(x) by x+1, we get the remainder p(-1) On putting x= -1 in Eq. (i), we get p(-1) = (-1)51 + 51 = -1 + 51 = 50 Hence, the remainder is 50.

Description : By actual division, find the quotient and the remainder when the first polynomial is divided by the second polynomial x4 + 1 and x-1. -Maths 9th

Last Answer : Actual division method

Description : By remainder theorem, find the remainder when p(x) is divided by g(x) -Maths 9th

Last Answer : Find the remainder when p(x) is divided by g(x)

Description : If the polynomials az3 +4z2 + 3z-4 and z3-4z + 0 leave the same remainder when divided by z – 3, -Maths 9th

Last Answer : Let p1(z) = az3 +4z2 + 3z-4 and p2(z) = z3-4z + o When we divide p1(z) by z - 3, then we get the remainder p,(3). Now, p1(3) = a(3)3 + 4(3)2 + 3(3) - 4 = 27a+ 36+ 9-4= 27a+ 41 When we ... to' the question, both the remainders are same. p1(3)= p2(3) 27a+41 = 15+a 27a-a = 15 - 41 . 26a = 26 a = -1

Description : The polynomial p{x = x4 -2x3 + 3x2 -ax+3a-7 when divided by x+1 leaves the remainder 19. -Maths 9th

Last Answer : p(x) is divided by x+ 2 =

Description : Find the remainder when y3 + y2 - 2y + 5 is divided by y - 5. -Maths 9th

Last Answer : Remainder = 145 Again, we should evaluate p(5) Let p(y) = y3 + y2 - 2y + 5 ∴ p(5) = 53 + 52 - 2 x 5 + 5 = 125 + 25 - 10 + 5 = 145 Thus , we find that p(5) is the remainder when p(y) is divided by y - 5 .

Description : Determine the remainder when polynomial p(x) is divided by x - 2 . -Maths 9th

Last Answer : p(x) = x4 - 3x2 + 2x - 5 According to remainder theorem, the required remainder will be = p(2) p(x) = x4 - 3x2 + 2x - 5 ∴ p(2) = 24 - 3(2)2 + 2(2) - 5 =16 - 12 + 4 - 5 = 3

Description : If x51 + 51 is divided by x + 1, then the remainder is -Maths 9th

Last Answer : (d) Let p(x) = x51 + 51 . …(i) When we divide p(x) by x+1, we get the remainder p(-1) On putting x= -1 in Eq. (i), we get p(-1) = (-1)51 + 51 = -1 + 51 = 50 Hence, the remainder is 50.

Description : By actual division, find the quotient and the remainder when the first polynomial is divided by the second polynomial x4 + 1 and x-1. -Maths 9th

Last Answer : Actual division method

Description : By remainder theorem, find the remainder when p(x) is divided by g(x) -Maths 9th

Last Answer : Find the remainder when p(x) is divided by g(x)

Description : If the polynomials az3 +4z2 + 3z-4 and z3-4z + 0 leave the same remainder when divided by z – 3, -Maths 9th

Last Answer : Let p1(z) = az3 +4z2 + 3z-4 and p2(z) = z3-4z + o When we divide p1(z) by z - 3, then we get the remainder p,(3). Now, p1(3) = a(3)3 + 4(3)2 + 3(3) - 4 = 27a+ 36+ 9-4= 27a+ 41 When we ... to' the question, both the remainders are same. p1(3)= p2(3) 27a+41 = 15+a 27a-a = 15 - 41 . 26a = 26 a = -1

Description : The polynomial p{x = x4 -2x3 + 3x2 -ax+3a-7 when divided by x+1 leaves the remainder 19. -Maths 9th

Last Answer : p(x) is divided by x+ 2 =

Description : If x to the power 11 + 101 is divided by x+1,what is the remainder? -Maths 9th

Description : Find the remainder when f(x)=4x(cube) - 12x(square) +14x - 3 is divided by g(x) = (2x-1). -Maths 9th

Last Answer : ____2x2-5x+4________________ 2x-1 ) 4x3-12x2+14x-3( 4x3-2x2 - + ____________ 0 -10x2+14x-3 ... + ___________ X+1

Description : Find the remainder when f(x)=9x(cube) -x 3x(square) + 14x - 3 is divided by g(x)=(3x-1). -Maths 9th

Description : If the polynomials az3 + 42z2 + 3z – 4 and z3 - 4z + a leave the same remainder when divided by z – 3, find the value of a. -Maths 9th

Description : If the expressions (px^3 + 3x^2 – 3) and (2x^3 – 5x + p) when divided by (x – 4) leave the same remainder, then what is the value of p ? -Maths 9th

Last Answer : Given that the following polynomials leave the same remainder when divided by (x - 4) : We are to find the value of a. Remainder theorem: When (x - b) divides a polynomial p(x), then the remainder is p(b). So, from (i) and (ii), we get Thus, the required value of a is 1.

Description : If x^3 + 5x^2 + 10k leaves remainder – 2x when divided by x^2 + 2, then what is the value of k ? -Maths 9th

Last Answer : x3+5x2+10k =(x2+2)(x+5)+10k−2x−10 ⇒10k−2x−10=−2x ⇒10k−10=0 or k=1.

Description : When (x^3 – 2x^2 + px – q) is divided by (x^2 – 2x – 3), the remainder is (x – 6), What are the values of p and q respectively ? -Maths 9th

Description : When a + b + c + 3a^(1/3) b^(2/3) + 3a(2/3) b^(1/3) is divided by a^(1/3) + b^(1/3) + c^(1/3), what is the remainder ? -Maths 9th

Description : If the polynomials ax^3 + 4x^2 + 3x – 4 and x^3 – 4x + a leave the same remainder when divided by (x – 3), the value of a is : -Maths 9th

Last Answer : Given ax^3 + 4x^2 + 3x - 4 and x^3 - 4x + a leave the same remainder when divided by x - 3. Let p(x) = ax^3 + 4x^2 + 3x - 4 and g(x) = x^3 - 4x + a By remainder theorem, if f(x) is divided by (x − a) then ... 4 27a+41 g(3)=27-4(3)+a 15+a f(3)=G(3) 27a+41=15+a 26a=15-41 a=15-41/26 a=-26/26 a=-1

Description : If the expression ax^2 + bx + c is equal to 4, when x = 0, leaves a remainder 4 when divided by x + 1 and leaves a -Maths 9th

Last Answer : Given exp. f(x) = ax2 + bx + c ∴ When x = 0, a.0 + b.0 + c = 4 ⇒ c = 4. The remainders when f(x) is divided by (x + 1) and (x + 2) respectively are f(–1) and f(–2). ∴ f( ... 2b = 2 ...(ii) Solving (i) and (ii) simultaneously we get, a = 1, b = 1.

Description : When x^40 + 2 is divided by x^4 + 1, what is the remainder ? -Maths 9th

Description : If the remainder of the polynomial a0 + a1x + a2x^2 + ....... + anx^n when divided by (x – 1) is 1, then which one of the following is correct ? -Maths 9th

Description : The remainder when 1 + x + x^2 + x^3 + ........ + x^(1007) is divided by (x – 1) is -Maths 9th

Description : When a polynomial f(x) is divided by (x – 3) and (x + 6), the respective remainders are 7 and 22. What is the remainder when f(x) is -Maths 9th

Description : If 9x^2 + 3px + 6q when divided by (3x + 1) leaves a remainder (-3/4) -Maths 9th

Last Answer : Given, (9x2 + 3px + 6q), when divided by (3x + 1) leaves a remainder −34−34 ∴ f(x) = 9x2 + 3px + 6q – (−34)(−34) = (9x2+3px+6q+34)(9x2+3px+6q+34) is exactly divisible by (3x + 1) ... ...(ii) Solving equations (i) and (ii), we get q = 0, p = 7474.

Description : The remainder, when x^(200) is divided by x^2 – 3^x + 2 is -Maths 9th

Description : When x^3 + 2x^2 + 4x + b is divided by (x + 1), the quotient is x^2 + ax + 3 and the remainder -Maths 9th

Description : If ax^3 + bx^2 + x – 6 has (x + 2) as a factor and leaves a remainder 4, when divided by (x – 2), the value of a and b respectively are : -Maths 9th

Last Answer : Let p(x) = ax³ + bx² + x - 6 A/C to question, (x + 2) is the factor of p(x) , and we know this is possible only when p(-2) = 0 So, p(2) = a(-2)³ + b(-2)² - 2 - 6 = 0 ⇒ ... --(2) solve equations (1) and (2), 4a = 0 ⇒a = 0 and b = 2 Then, equation will be 2x² + x - 6

Description : what is 2151 divided by 2 and the remainder?

Description : A bakery bakes 15 batches of 29 cupcakes each week. How many individual cupcakes do they make each week What is the remainder when 57 is divided by 6?

Description : What is the remainder of 755 divided by 7 and what is the answer to it too Long Division?

Description : what the remainder of 689 divided by 16?

Description : What is 76 divided by 5 remainder?

Description : What is 57 divided by 7 with remainder?

Description : what is the remainder for 859 divided by 3?

Last Answer : It is 286 and remainder 1

Description : What is 87 divided by 33(with remainder)?